Health and environmental co-benefits and conflicts of actions to meet UK carbon targets. (2nd April 2016) - Smith, Alison C.; Holland, Michael; Korkeala, Outi; Warmington, Jamie; Forster, Daniel; ApSimon, Helen; Oxley, Tim; Dickens, Roald; Smith, Stephen M.
Abstract : Many actions to reduce GHG emissions have wider impacts on health, the economy, and the environment, beyond their role in mitigating climate change. These ancillary impacts can be positive (co-benefits) or negative (conflicts). This article presents the first quantitative review of the wider impacts on health and the environment likely to arise from action to meet the UK's legally-binding carbon budgets. Impacts were assessed for climate measures directed at power generation, energy use in buildings, and industry, transport, and agriculture. The study considered a wide range of health and environmental impacts including air pollution, noise, the upstream impacts of fuel extraction, and the lifestyle benefits of active travel. It was not possible to quantify all impacts, but for those that were monetized the co-benefits of climate action (i.e. excluding climate benefits) significantly outweigh the negative impacts, with a net present value of more than £85 billion from 2008 to 2030. Substantial benefits arise from reduced congestion, pollution, noise, and road accidents as a result of avoided journeys. There is also a large health benefit as a result of increased exercise from walking and cycling instead of driving. Awareness of these benefits could strengthen the case for more ambitious climate mitigation action. Policy relevance This article demonstrates that actions to mitigate GHG emissions have significant wider benefits for health and the environment. Including these impacts in cost–benefit analysis would strengthen the case for the UK (and similar countries) to set ambitious emissions reduction targets. Understanding co-benefits and trade-offs will also improve coordination across policy areas and cut costs. In addition, co-benefits such as air quality improvements are often immediate and local, whereas climate benefits may occur on a longer timescale and mainly in a distant region, as well as being harder to demonstrate. Dissemination of the benefits, along with better anticipation of trade-offs, could therefore boost public support for climate action.